First Case of Ewingella americana Meningitis in a Term Newborn: A Rare but Real Pathogen - Meisler, Sarah; Kamity, Ranjith; Noor, Asif; Krilov, Leonard; Tiozzo, Caterina (Frontiers in Pediatrics, 2020)
Ewingella americana is a Gram-negative, catalase positive and anaerobic enterobacterium first de-scribed in 1983. Infections caused by this pathogen, such as bacteremia and pneumonia, are ex-tremely rare and primarily occur in patients with underlying pathologies or immunosuppression. There is still a debate as to whether Ewingella americana is a real pathogen or if it can be consid-ered an opportunistic infectious agent. We report the first documented case of Ewingella americana meningitis in literature and the first case of this pathogen causing infection in a newborn. Case presentation: A term newborn male was born via spontaneous vaginal delivery to a Gravida 2 Para 0, 28 year old woman with negative prenatal screening tests with a birth weight of 4.70g kilograms and Ap-gar scores of 9 and 9 at 1 and 5 minutes respectively. Rupture of membranes was 27 hours prior to delivery. Infant was noted to be febrile to 101°F at birth, so infant was admitted in the neonatal in-tensive care unit and started empirically on ampicillin and gentamycin. Cerebrospinal fluid (CSF) drawn due to irritability on day of life 1 presented normal cell and protein count but grew Gram negative rods after 2 days, identified subsequently as Ewingella americana; repeat CSF analysis done at 6 days of life showed pleocytosis. Brain MRI performed at 2 weeks of life showed lep-tomeningitis. The infant was treated with ceftazidime for 21 days from the first negative CSF cul-ture. He has since followed up with the neurologist and infectious disease specialist. He had a normal electroencephalogram (EEG) and is meeting all developmental milestones at the 15 24 months of age follow up visit. Conclusion: Our case highlights that Ewingella americana can cause serious invasive infections such as menin-gitis in the neonatal period with minimal symptomatology. Antibiotic treatment in the neonatal peri-od can present challenges due to the Ewingella americana ’s variable sensitivity. The role of these emerging low virulence organisms in causing infections has to be further elucidated, especially in vulnerable patients such as newborns.